UNFETTERED, BUT NOT UNBRIDLED: THE FIDUCIARY DUTY OF THE TRUSTEE Wiid v Wiid NCHC (unreported) 13-01-2012 Case no 1571/2006 - Eben Nel (Obiter, 2016)
The fiduciary duty and accompanying discretionary power of the trustee in South African trust law is considered, with particular reference to its application in Wiid v Wiid. The contents and exercise of trustees’ discretion in light of the fiduciary duty are examined and applied to the particular judgment. The conventional attribution by trust deeds of an unfettered trustee discretion is proved to be subject both to the limitations inherent to the fiduciary duty and the unique nature of the trust figure. It is submitted that, notwithstanding some equivocal statements by the court, valuable lessons for trustees can be taken from the matter in casu.